Civil Law Aspects of Child Protection Due to Early Marriage - Wahdaniah Baharuddin (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2025)
Early marriage remains a concerning phenomenon in West Sulawesi Province despite the minimum age requirement of 19 years as stipulated in Law Number 16 of 2019 on Marriage. The frequent granting of marriage dispensation by the courts weakens the principle of child protection as mandated by Law Number 35 of 2014 on Child Protection. This study aims to analyze the civil law consequences arising from early marriage and to assess the extent to which Indonesia’s positive legal instruments provide effective protection for children in West Sulawesi. This research employs a normative juridical method with statutory and conceptual approaches. Data were obtained through library research involving primary, secondary, and tertiary legal materials, which were analyzed using a qualitative descriptive method. Early marriage results in uncertainty regarding the civil status of the child, weak parental responsibilities, and violations of the principle of legal capacity. The implementation of civil law norms in West Sulawesi remains ineffective due to cultural, economic, and educational factors. Strengthening substantive and humanistic civil law mechanisms is therefore necessary to ensure fair and effective child protection.